2020
DOI: 10.1161/circep.120.008651
|View full text |Cite
|
Sign up to set email alerts
|

Complete Electroanatomic Imaging of the Diastolic Pathway Is Associated With Improved Freedom From Ventricular Tachycardia Recurrence

Abstract: Background - The development of multielectrode mapping catheters has expanded the spectrum of mappable ventricular tachycardias (VTs). Full diastolic pathway recording has been associated with a high rate of VT termination during radiofrequency (RF) ablation as well as non inducibility at study end. However, the role of diastolic pathway mapping on VT recurrence has yet to be clearly elucidated. We aimed to explore the role of complete diastolic pathway activation mapping on VT recurrence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…The utility of VT activation mapping has been recently described. 19,20 Hadjis et al 19 showed that VT recurrence was significantly lower among those patients with complete delineation of the diastolic pathway (12%) during VT when compared with partial or no recording of the diastolic pathway (50% and 45%, respectively, p = .02).…”
Section: Utility Of Baseline Inducibility and Activation Mapping During Vt Ablationmentioning
confidence: 99%
“…The utility of VT activation mapping has been recently described. 19,20 Hadjis et al 19 showed that VT recurrence was significantly lower among those patients with complete delineation of the diastolic pathway (12%) during VT when compared with partial or no recording of the diastolic pathway (50% and 45%, respectively, p = .02).…”
Section: Utility Of Baseline Inducibility and Activation Mapping During Vt Ablationmentioning
confidence: 99%
“…The benefit of catheter ablation in reentrant VT patients with structural heart disease is wellknown, with freedom from recurrence approaching 70% (188). However, the success rate with this procedure has plateaued, despite advances in both mapping catheter technology and electroanatomic mapping systems (188,189).…”
Section: Future Directions For Mapping and Ablation Of Circuit Morphologiesmentioning
confidence: 99%
“…The benefit of catheter ablation in reentrant VT patients with structural heart disease is wellknown, with freedom from recurrence approaching 70% (188). However, the success rate with this procedure has plateaued, despite advances in both mapping catheter technology and electroanatomic mapping systems (188,189). High density multi-electrode catheters can enhance the possibility of detailed activation mapping of even poorly tolerated VTs because they can be produced in a reasonable time frame.…”
Section: Future Directions For Mapping and Ablation Of Circuit Morphologiesmentioning
confidence: 99%
“…Electrophysiological studies, through the acquisition of endocavitary signals, aim at recognizing those arrhythmogenic regions, which can form localized or macro‐reentry circuits. Activation maps and EGMs morphology reveal the presence of areas of slowing (fibrotic tissue) and conduction blocking (scar tissue) 45,46 . The mathematical analysis of these data, in the form of biomarkers calculation, provides a first quantitative tool in support of the electrophysiologist 9 .…”
Section: Pathological Conditionsmentioning
confidence: 99%